Analisis Faktor-Faktor yang Mempengaruhi Minat Bertransaksi Masyarakat Non Muslim pada Bank Syariah (Studi pada Bank Syariah) - Siti Arawiyyah Ardi; Maulana Alghifari; Restu Tumanggor; Enika Diana Batubara (Universitas Muhammadiyah Surabaya, 2023)
AbstrakIslamic banks are sharia-based intermediaries that serve both Muslims and non-Muslims. The Islamic banking system is based on a profit-sharing system, namely a modern, universal, and open Islamic banking system for all Indonesian people. The domestic industrial market is heterogeneous and has different beliefs. Islamic banking in Indonesia is growing and developing, although its market share is still small at around 4.9%. This study analyzes the factors that influence the interest of non-Muslim students in doing business in Islamic banks. The results of the study show that the factors that influence Islamic bank transactions are. variable information, product, price and promotion, clearly have a positive effect. However, the location variable does not have a significant positive effect.Keywords: Islamic Banks, Non-Muslims, Multiple Linear Regression.